(untitled) (INTERNATIONAL SCIENTIFIC-ELECTRONIC JOURNAL “PIONEERING STUDIES AND THEORIES”, 2025)
This article explores the evolution of the decent work concept in Uzbekistan, analysing its transformation from the legacy of the planned economy to the challenges and opportunities associated with digitalization. The paper reveals how the understanding and implementation of decent work principles formulated by the International Labour Organization (ILO) have adapted to the unique socio-economic conditions of the country. The author traces the key stages: from the formal provision of employment in the Soviet period to the difficult conditions of the transition period and, finally, to modern reforms aimed at liberalization and digitalization of the labour market. Particular attention is paid to the impact of digital technologies on employment, wages, social protection and social dialogue. The methodological basis of the study was historical and comparative analysis, systems approach and statistical data. The results show that, despite significant progress, Uzbekistan faces the need to further adapt the institutional environment and educational system to ensure decent work in the context of a rapidly changing digital economy.